Cognitive Load of University Students and its Relationship to their Academic Achievement - Meeaad Jasim Salman Al-Sarry; Ban Hassan Majeed; Safa Khudhair Kareem (Periodica Journal, 2022)
The research aims to identify the amount of cognitive load among students of the Department of Mathematics with level of academic achievement in general mathematics information; and the relationship between cognitive load and academic achievement in general mathematics information. The sample consisted of (200) male and female students from the Department of Mathematics who were chosen randomly. To achieve the objectives of the research, a tool was built to measure the cognitive load consisted of (21) items, and the validity and reliability of the tool were verified authenticity and constancy by using (percentage, Pearson correlation coefficient and one-sample t-test) as statistical means. It was concluded that the research sample has a cognitive burden. The mathematical activities, skills and tasks practiced by the students of the mathematics department contribute to increas the cognitive load. They possess a comprehensive mathematical knowledge of concepts, skills, principles and problems, which represents their academic achievement in mathematics. The cognitive load is positively correlated with academic achievement. The researchers came up with a set of recommendations and suggestions
Keywords: Cognitive; achievement; Academic; University